AN ANALYSIS OF DIFFICULTIES IN ONLINE ENGLISH LEARNING EXPERIENCED BY THE EFL TEACHER - Ahmed Sardi; Muhammad Firmansyah JN; Abdul Walid; Andi Kamal Ahmad (Institut Agama Islam Negeri Parepare, 2022)
The purpose of this research was to describe the analysis of difficulties in Online English Learning experienced by the EFL teacher at SMP 5 Parepare. This research used descriptive qualitative method with the population in this research was the English teacher at SMPN 5 Parepare. The sample technique used was totally sampling so that the sample of 4 English teachers obtained. Data collection techniques used in this research were interviews and voice recordings. The research of data analysis from Interview showed that the way the English Teacher delivered the class by online system in this pandemic covid-19. It was dominated by the using of learning applications as media of this new learning method. All of the English teacher at SMP 5 Parepare used WhatssApp application to delivered their class by using another application to prepare the materials. The students used the specific learning application for examination or task such as G-Form and Quizizz. The writer found some troubles/difficulties experienced by the English teachers at SMP 5 Parepare. The troubles/difficulties experienced by the English teachers at SMP 5 Parepare such as, network constraints, limited internet quota, there are some students who do not have their own learning tools in the form of mobile phone or Laptop, and the lack of enthusiasm of the students themselves. The students who lack of response in this case, could be the students those do not have mobile phone or laptop. So, it was started from the cause that is the student do not have private online learning tools.